Hubungan Praktik Self Care dengan Kesejahteraan Psikologis Ibu Nifas di Wilayah Kerja Puskesmas Lubuk Buaya Kota Padang - Darma, Ika Yulia; Khaula, Wahna; Zaimy, Silvi; Idaman, Meldafia; Moryanda, Rury; Indriani, Silfina (Jurnal Ners, 2025)
The postpartum period is a critical recovery phase for mothers that involves significant physiological and psychological changes. Inadequate adaptation during this period can affect the psychological well-being of mothers, increasing the risk of postpartum depression, baby blues, or even psychosis. One important factor contributing to maternal psychological well-being is self-care practice, which refers to the mother’s ability to care for herself independently. This study aimed to examine the relationship between self-care practices and the psychological well-being of postpartum mothers in Pasia Nan Tigo Village, within the Lubuk Buaya Public Health Center working area, Padang City. This research employed a quantitative method with a cross-sectional approach and total sampling technique. A total of 32 postpartum mothers were included in the study. Data were collected using structured questionnaires and analyzed using the Chi-Square test. The findings revealed that 85.7% of respondents had poor self-care practices, and most of them were at risk of psychological distress. Statistical analysis confirmed a significant relationship between self-care practices and psychological well-being (p < 0.05). This study highlights the importance of educational support and promotion of self-care practices to enhance maternal psychological health in the postpartum period.